Changing sense of place in hybrid work environments: A systematic review of place identity and employee well-being - Meng Sun; Thomas Kraus; Roman Pauli; Cyryl Garus (Wellbeing, Space and Society)
The concept of ''sense of place'' refers to an individual's subjective perception and emotional attachment to a specific geographic location. It encompasses a multidimensional and complex experience that is influenced by various social, cultural, historical, and ecological factors. However, the increasing prevalence of hybrid and location-flexible work arrangements poses a potential challenge to this concept. The primary aim of this study is to conduct a comprehensive literature review, focusing on the multifaceted nature of sense of place and the potential transformation of employees' place identity in response to hybrid work. Through a systematic search of four academic databases, fourteen empirical studies were identified and included based on predetermined inclusion criteria following established systematic review guidelines. Our content analysis revealed three key findings: (1) seven critical factors that shaped employee identity in hybrid work environments; (2) four distinct states of workplace identity adaptation—home-oriented, work-oriented, integrated, and virtual; and (3) the dual effects of identity changes on employee well-being. The findings contribute to understanding identity dynamics and their implications for employee well-being in hybrid work arrangements while providing practical insights for organizations to enhance sense of place in hybrid work environments.